(untitled) (Repertorio Científico, 2023)
Costa Rican education has been in constant change for some years and this means that adaptation processes respond in a timely manner to such changes. From a social action project registered at the University of Costa Rica, efforts are made to contribute to the continuous improvement of mathematics education at the primary level through the generation and execution of teaching strategies and training processes that support teaching work and the promotion of mathematical abilities and skills in both the teaching staff and the students with the purpose of laying the mathematical foundations that allow them to function better at other levels of the Costa Rican educational system. The objective of this study is to present the results generated with the application of these training processes.